Pressotherapy as a factor of performance improvement academic rowers - Artemenko E.P.; Miftakhov S.F. (Theory and Practice of Physical Culture, 2025)
Physical recreation plays a vital role in the lives of combat veterans, aiding in their physical and psychological recovery and facilitating successful reintegration into society. Regular physical activity helps veterans address various challenges stemming from their participation in military operations. This study examines the key aspects of physical recreation that contribute to restoring physical fitness and psychological stability among combat veterans returning from special military operations. The findings highlight that physical activity restores strength, endurance, flexibility, and coordination, particularly for veterans with injuries or disabilities, through adapted training programs. Exercise also reduces stress, anxiety, and depression by boosting endorphin production, improving mood, and fostering emotional stability. Group activities enhance socialization, helping veterans overcome isolation. Additionally, regular exercise alleviates chronic pain, improves sleep quality, and promotes overall well-being. The study emphasizes the importance of tailored physical activities, such as adapted physical education, cardiovascular training, strength exercises, yoga, Pilates, group sports, and outdoor activities, based on individual needs and preferences. A sociological survey conducted at the Kazan Higher Tank Command School (October 2024) among cadets aged 21–30 revealed that 50% prioritize family and outdoor recreation, 30% focus on socializing with friends, and 20% regularly engage in physical activity to restore their physical and mental health. In conclusion, physical recreation serves as a crucial tool for the rehabilitation and reintegration of combat veterans, enabling them to reclaim a fulfilling life.